Relationship between average slope of textured substrate and poly-Si thin film solar cells performance - Muhida, Riza; Sutjipto, Agus Geter Edy; ., Afzeri; Toyama, T.; Okamoto, Hiroaki (Maney Publishing, 2009)
This paper presents a nanoscopic characterisation of a series of textured substrates with a structure of Ag-grid/ZnO/p-i-n/ZnO/Ag/SnO2/glass for poly-Si thin film solar cells performed by atomic force microscopy, in order to find the optimum texture substrate and realise the light trapping. The relationship between average slopes (tanh) and photovoltaic performance are studied based on the experimental results. The experimental results show that the textured ZnO/Ag/SnO2/glass with tanh of 0?13 yields the maximum conversion efficiency for Jsc and Voc. Although the poly-Si deposited on highly textured substrate (s.37 nm) shows excellent light trapping properties, however, in its microstructure shows a crystal deterioration and exhibits ntype characteristic, yielding poor photovoltaic performances.